How is the Existence of Urban Villages in the Economic Dynamics of Metropolitan Areas? - Lestari, Endah Kurnia; Nugroho, Satrio Candra; Naba, Faikar Mahdiy Izzatan; Putra, Aditya Ferdama; Kasih, Sekar Wulan Amboro (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
Urban villages in Indonesia are unique socio-economic entities that reflect local History, identity, and community-based economic practices amid metropolitan expansion. Rapid urbanization and modernization generate pressures such as gentrification, land conversion, rising property values, spatial segregation, and economic marginalization, threatening livelihoods and weakening traditional social structures. This study analyzes the urgency of strengthening the urban village economy and strategies for integrating it into a dynamic metropolitan system characterized by spatial transformation and rapid policy change. Using a qualitative approach through a Systematic Literature Review, this research identifies, evaluates, and synthesizes relevant academic and policy sources in a structured and transparent manner. The findings indicate that urban villages possess significant economic potential, including micro enterprises, creative economy activities, informal sector initiatives, and strong local social networks. These potentials can be enhanced through technological innovation, business digitalization, capacity building, and inclusive urban planning. Nevertheless, limited access to infrastructure, financing, formal markets, and public services remains a major barrier to economic transformation. The study concludes that integration into metropolitan policy must prioritize local economic resilience through spatial protection, UMKM empowerment, participatory planning, and collaborative governance to achieve inclusive and sustainable urban development.